Checkpoint â€“ An Online Descriptive Answers Grading Tool (International Journal of Advanced Research in Computer Science, 2017)
We live in an age of technology. Everything is automated. Even in the field of education, the use of technology is increasing largely. However, even today exams where theoretical questions need to be answered are taking place manually. This is because little work progress has been made in the field of grading theoretical answers written by students during examinations. Hence, we plan on creating an application that will help in evaluating answers. We call this application â€œCheckpointâ€. It is a natural language processing based descriptive answer checking and grading application. This application would simulate human thinking for assessing descriptive answers using natural language processing. NLP involves natural language understanding that is, enabling computers to derive meaning from human or natural language input, and produce the desired output. This application would first parse the answer that is given as an input to it. Taking into consideration for the presence of synonyms it will check how similar the given answer is to the ideal answer whose keywords will be provided by the teachers. Depending on the similarity, it will grade the answers. Keywords: Exams, paper checking, assessment, online examination, grading, theoretical answers analysis